Predictors of long-term outcomes of coronary bifurcation stenting: 6-year results from international, randomized POLBOS I and POLBOS II clinical trials. (25th November 2020) - Gil, R.J; Kern, A; Inigo Garcia, L.A; Formuszewicz, R.J; Dobrzycki, S; Vassilev, D; Bil, J
Abstract: Introduction: Bifurcation lesions pose a therapeutic challenge during percutaneous coronary intervention (PCI). Results of regular drug-eluting stents (rDESs) in bifurcation treatment are not optimal. Purpose: The aim of this study was to analyze the 6-year follow-up of BiOSS (Balton, Poland) stents in patients enrolled into two randomized clinical trials POLBOS I (NCT02192840) and POLBOS II NCT02198300). Methods: The BiOSS stent is a coronary dedicated bifurcation balloon expandable stent made of 316L stainless steel and coated with a biodegradable polymer as well as the drug. The stent consists of two parts with different diameters connected with two struts of 1.9 - 2.5 mm length each. The aim of randomized POLBOS trials was to compare the BiOSS stents with regular drug eluting stents (rDES) in patients with stable CAD or NSTE-ACS (POLBOS I: paclitaxel eluting BiOSS Expert vs rDES; POLBOS II: sirolimus eluting BiOSS LIM vs rDES). Provisional T-stenting was the default strategy. Angiographic control was performed at 12 months in all patients. The primary end-point was composed MACE defined as cardiac death, myocardial infarction or target lesion revascularization (TLR). Clinical assessment was performed every year after index procedure. Results: In POLBOS I trial BiOSS Expert was implanted in 120 patients (49.4%), and rDES was implanted in 123 patients. The target vessel was the left anterior descending (LAD) artery (52% vs 70%) followed by the left main stem (LMS) coronary artery (22% vs 15%). In rDES group, 38.2% of patients received paclitaxel-eluting stents. Side branch treatment with rDES was required in 10% of cases in both groups. At 12 months, the incidence of cumulative major adverse cardiovascular events (MACE) was similar in both groups: 13.3% vs 12.2% (P=0.7). The TLR rate was significantly higher in the BiOSS Expert group compared with rDES group (11.5% vs 7.3%; P=0.02). Significantly lower rates of restenosis were observed in final kissing balloon (FKB) subgroups of both the BiOSS Expert (8.1% vs 13.2%; P<0.05) and rDES groups (4.9% vs 9.5%; P<0.05). In POLBOS II 202 patients were randomly assigned 1:1 to treatment of the coronary bifurcation lesions either with the BiOSS LIM stent (n=102) or with rDES (n=100). The target vessel was the LAD (44% vs 43%) followed by the LMS (35.3% vs 38%). Side branch treatment was required in 8.8% (rDES) and 7% (BiOSS). At 12 months, the cumulative MACE incidence was similar in both groups (11.8% [BiOSS] vs. 15% [rDES, p=0.08]), as was the TLR rate (9.8% vs. 9% [p=0.8]). The binary restenosis rates were significantly lower in the FKBI subgroup of the BiOSS group (5.9% vs. 11.8%, p<0.05). At the time of ESC Congress 2020 we will present data from 6-year follow-up from POLBOS I trial and POLBOS II trial focusing on LM stenting and patients with diabetes. Conclusions: BiOSS® stents provided satisfactory 1-year results which seemed comparable with rDES. Long-term data are pending. Funding Acknowledgement: Type of funding source: None